IMPROVING STUDENTS™ ACHIEVEMENT IN WRITING NARRATIVE TEXT THROUGH THINK-PAIR-SHARE TECHNIQUE - Saragih, Zulfida Sari (Universitas Negeri Medan, 2012)
This study was focused to improve students™ achievement in writing narrative test through Think-Pair-Share Technique. It was conducted by applying Classroom Action Research with two cycles and six meetings. The subject of this study is Grade VIII students of SMP Negeri 1 Teluk Mengkudu and consisted of 40 students. The instruments for collecting data used writing test for quantitative and used diary notes, observation sheet and interview sheet for qualitative. The mean of the test shows the improvements of the students™ score for orientation test was (51.4), the mean in cycle I test was (66.15), and the mean in the cycle II was (74.57). Based on the data above, it can be concluded that Think-Pair-Share technique is significantly improved students™ writing achievement especially in narrative test. Key Words: Improving, Achievement, Writing, Narrative,Think-Pair-Share